Dietary nitrate supplementation and exercise performance: an umbrella review of 20 published systematic reviews with meta-analyses - Poon, E. T.-C.; Iu, J. C.-K.; Sum, W. M.-K.; Wong, P.-S.; Lo, K. K.-H.; Ali, A.; Burns, S. F.; Trexler, E. T. (Sports Medicine, 2025)
Background: Dietary nitrate (NO3-) supplementation is purported to benefit exercise performance. However, previous studies have evaluated this nutritional strategy with various performance outcomes, exercise tasks, and dosing regimens, often yielding inconsistent results that limit the generalizability of the findings. Objective: We aimed to synthesize the available evidence regarding the effect of NO3- supplementation on 11 domains of exercise performance. Methods: An umbrella review was reported in accordance with the Preferred Reporting Items for Overviews of Reviews guideline. Seven databases (MEDLINE, EMBASE, Cochrane Database, CINAHL, Scopus, SPORTDiscus, and Web of Science) were searched from inception until July 2024. Systematic reviews with meta-analyses comparing NO3- supplementation and placebo-controlled conditions were included. Literature search, data extraction, and methodological quality assessment (A Measurement Tool to Assess Systematic Reviews Assessing the Methodological quality of SysTemAtic Review [AMSTAR-2]) were conducted independently by two reviewers. Results: Twenty systematic reviews with meta-analyses, representing 180 primary studies and 2672 unique participants, met the inclusion criteria. Our meta-analyses revealed mixed effects of NO3- supplementation. It improved time-to-exhaustion tasks [standardized mean difference (SMD): 0.33; 95% confidence interval (CI) 0.19-0.47] with subgroup analyses indicating more pronounced improvements when a minimum dose of 6 mmoL/day (372 mg/day) and chronic (> 3 days) supplementation protocol was implemented. Additionally, ergogenic effects of NO3- supplementation were observed for total distance covered (SMD: 0.42; 95% CI 0.09-0.76), muscular endurance (SMD: 0.48; 95% CI 0.23-0.74), peak power output (PPO; SMD: 0.25; 95% CI 0.10 to 0.39), and time to PPO (SMD: - 0.76; 95% CI - 1.18, - 0.33). However, no significant improvements were found for other performance outcomes (all p > 0.05). The AMSTAR-2 ratings of most included reviews ranged from low to critically low. Conclusions: This novel umbrella review with a large-scale meta-analysis provides an updated synthesis of evidence on the effects of NO3- supplementation across various aspects of exercise performance. Our review also highlights significant methodological quality issues that future systematic reviews in this field should address to enhance the reliability of evidence.